Soilless Culture Applications for Early Development of Soybean Crop (Glycine max L. Merr) - Rosnani Abd Ghani; Suhana Omar; Márton Jolánkai; Ákos Tarnawa; Zoltán Kende; Noriza Khalid; Csaba Gyuricza; Mária Katalin Kassai (Agriculture, 2023)
Soilless cultivation systems in a controlled environment are increasingly being used due to several global issues such as climate change, pest and disease problems, declining soil fertility quality and limited agricultural land. Soybean is one of the potential crops that can be grown using the soilless planting system in a controlled environment. Therefore, a study was conducted to investigate the effect of nutrient concentrations on the early development of two soybean varieties. Four different nutrient concentrations (0%, 50%, 100% and 150%) were applied, and two soybean varieties (Martina and Johanna) were tested. This study was designed in a split-plot experimental design where the nutrient concentration was the main plot and the variety was the sub-plot. The data record was started after fertilization. The plant growth data were collected for five weeks. All the data were analyzed statistically using SPSS V.23 software. The results of the study found that the nutrient concentration affected the number of leaves and leaf area. The number of leaves was higher in the treatment using 100% and 150% nutrients. Meanwhile, the leaf area increased with increasing nutrient concentration from 0% to 150%. The nutrient concentration then interacted with the variety in influencing the plant height. The plant height of the Martina variety was higher than the Johanna variety when 0% and 100% nutrients were applied. The variety also affected the leaf area and interacted with the number of weeks in affecting the SPAD readings and number of leaves. Thus, the two tested varieties (Johanna and Martina) have distinct early growth patterns that differ from one another as affected by the nutrient concentrations and plant age (number of weeks).